MODELING OF MECHANISM OF STRENGTHENING LAYER FORMING IN THE PROCESSES OF HARDENING AND RECOVERY OF STEEL ARTICLES BY MEANS OF FROSTING - A. V. Alifanov; G. F. Betenja; V. M. Golub (Литьë и металлургия)
The mathematical model of the process of diffusion silvering of reinforcing layer on steel articles, reflecting interference of main technological parameters of the process is developed. Algorithm of solving of Stefan problem at not specified initially temperature of contact of billet and crystallized melt is offered.